Targeted Reducing of Tauopathy Alleviates Epileptic Seizures and Spatial Memory Impairment in an Optogenetically Inducible Mouse Model of Epilepsy - Gao, Yang; Zheng, Jie; Jiang, Tao; Pi, Guilin; Sun, Fei; Xiong, Rui; Wang, Weijin; Wu, Dongqin; Li, Shihong; Lei, Huiyang; Yu, Huiling; Zhou, Qiuzhi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Intracellular deposition of hyperphosphorylated tau has been reported in the brain of epilepsy patients, but its contribution to epileptic seizures and the association with spatial cognitive functions remain unclear. Here, we found that repeated optogenetic stimulation of the excitatory neurons in ventral hippocampal CA1 subset could induce a controllable epileptic seizure in mice. Simulataneously, the mice showed spatial learning and memory deficits with a prominently elevated total tau and phospho-tau levels in the brain. Importantly, selective facilitating tau degradation by using a novel designed proteolysis-targeting chimaera named C4 could effectively ameliorate the epileptic seizures with remarkable restoration of neuronal firing activities and improvement of spatial learning and memory functions. These results confirm that abnormal tau accumulation plays a pivotal role in the epileptic seizures and the epilepsy-associated spatial memory impairments, which provides new molecular target for the therapeutics.